Instruments for Measuring Career Decision Self-Efficacy in High School Students: A Systematic Literature Review - Nurrizki Shafira; Agus Taufiq; Nandang Budiman; Uman Suherman; Ferianti (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
In the field of career development, career decision-making self-efficacy plays an important role in adolescents' career decision-making process, decision-making ability, career exploration behaviour, performance goals, and career identity. The main objective of this review was to identify and analyse the instruments used by researchers to measure high school students' CDSE. Using the Systematic Literature Review method, the researcher specifically identified Scopus-indexed articles published between 2003 and 2023. The authors found that the Career Decision Self-Efficacy Scale Short Form (CDSES-SF), developed by Betz, Klein, & Taylor (1996), is the most widely used instrument to measure career decision self-efficacy. The CDSES-SF shows high reliability, with Cronbach's alpha ranging from α=0.78-0.95, placing it in the good and excellent categories. In addition, the CDSES-SF has been applied to diverse high school students from different races, ethnicities, ages, grade levels, skin colours, genders, and countries. Keywords: career decision self-efficacy, high school students, a systematic literature review, instrument